Manajemen Program Pembiasaan Membaca Al-Quran di SMP Negeri 24 Medan - Bunaiya, Khairun Nisa; Fanreza, Robie (Yayasan Rahmat Islamiyah, 2024)
This research is motivated by the lack of interest of students in starting themselves in getting used to reading the Koran every day and students having difficulty reading the Koran properly and correctly. The ability to read the Koran in students is very lacking. Character education from parents is very significant in shaping students' cognitive intellectuals, but there are still many parents who do not have time for their children so that their children's education is less than optimal. The ability and interest of students in reading the Al-Quran is described as low. Routine activities to get used to reading the Qur'an do the effect can produce different results of students' abilities and activities. This research was conducted at SMP Negeri 24 Medan. The observation method is carried out to receive data related to research, with the observation method researchers can find out students' interests in getting used to and reading the Al-Quran every day. Efforts to cultivate habits in the importance of Al-Qur'an education in early childhood at SMP Negeri 24 Medan really need to be implemented. From habits in learning the Koran to be a reference to shape the character of students so that they have better moral.